2017
DOI: 10.1111/cdev.12912
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Physiological and Affective Responding to Infant Distress: Unique Antecedents of Avoidant and Resistant Attachments

Abstract: In a sample of 127 mother-infant dyads, this study examined the predictive significance of mothers' physiological and observed emotional responding within distressing and nondistressing caregiving contexts at 6 months for infant attachment assessed with Fraley and Spieker's (2003) dimensional approach and the categorical approach at 12 months. Findings revealed that a lesser degree of maternal respiratory sinus arrhythmia withdrawal and higher levels of maternal neutral (vs. positive) affect within distressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Allostatic load can take the direction of either hyperactivity, that is, a failure to shut down the stress system, or hyporeactivity, that is, a failure to mobilize a stress response, resulting in a blunted pattern of responses. In this study, we found evidence for the latter, consistent with other studies reporting blunted RSA or HRV responsiveness during distress interaction with own infants (Groh et al, in press; Leerkes, Su, Calkins, O'Brien, & Supple, 2017; Schechter, Moser, McCaw, & Myers, 2014). While in the current study no support was found for a mechanism that involved the sympathetic nervous system, it may be premature to dismiss its role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Allostatic load can take the direction of either hyperactivity, that is, a failure to shut down the stress system, or hyporeactivity, that is, a failure to mobilize a stress response, resulting in a blunted pattern of responses. In this study, we found evidence for the latter, consistent with other studies reporting blunted RSA or HRV responsiveness during distress interaction with own infants (Groh et al, in press; Leerkes, Su, Calkins, O'Brien, & Supple, 2017; Schechter, Moser, McCaw, & Myers, 2014). While in the current study no support was found for a mechanism that involved the sympathetic nervous system, it may be premature to dismiss its role.…”
Section: Discussionsupporting
confidence: 92%
“…Because the study did not include measurement of ANS responses to caregiving for the mothers’ own children, it remains to be established to what extent the paradigm elicited responses that also occur in real caregiving interactions. However, blunted parasympathetic responses to actual child distress have been found to be associated with both maternal posttraumatic stress disorder (Schechter et al, 2014) and insecure parent–infant attachment (Groh et al, in press; Leerkes et al, 2017), supporting blunted parasympathetic nervous system reactivity as part of mechanisms linking adversity in caregiving experiences to the socioemotional context of children's development.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed early mother–child attachment security with the Attachment Behavior Q-Sort (AQS; Waters and Deane, 1985 ), which yields a continuous score for attachment security rather than assignment to a particular attachment category. This approach maximizes statistical power by affording excellent detection of fine individual differences, and may be especially appropriate in the context of small sample sizes ( Groh et al, 2017b ). Psychometric work also suggests that a dimensional approach is coherent with the underlying structure of individual differences in attachment ( Fraley and Spieker, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Authoritarian style is a part of overparenting, which comprises two related aspects of over-controlling and overprotection (16). Furthermore, previous studies have found that over-controlling parents are more prone to depression and overprotective parents are more prone to anxiety (17). Bahrami et al (18) showed the relationship between parental emotions and interacting with children and upbringing in mothers of preschool children.…”
Section: Discussionmentioning
confidence: 99%